Immune responsiveness in stable kidney transplantation patients: Complete inhibition of T‐cell proliferation but residual T‐cell activity during maintenance immunosuppressive treatment - Aliede E. in 't Veld; Boukje C. Eveleens Maarse; Maria J. Juachon; Soufian Meziyerh; Aiko P. J. deVries; Aline L. vanRijn; Mariet C. W. Feltkamp; Dirk Jan A. R. Moes; Jacobus Burggraaf; Matthijs Moerland (Wiley, 2024)
Abstract The recommended immunosuppressive treatment after kidney transplantation consists of tacrolimus, mycophenolate mofetil, and low‐dose corticosteroids. Drug concentrations are monitored using therapeutic drug monitoring (TDM), which does not necessarily correlate with pharmacodynamic activity. To find the balance between optimal efficacy and minimal toxicity, it might be more informative to monitor patients' immunological status rather than drug concentrations. We selected a panel of T‐cell‐based immune assays, which were used for immunomonitoring of 14 stable kidney transplantation patients. Whole blood was incubated with a T‐cell stimulus, after which T‐cell proliferation, T‐cell activation marker expression and cytokine production were measured to study residual immune activity in vitro (before drug intake; drug added to the incubation) and ex vivo (after drug intake). T‐cell proliferation was completely suppressed in all patients over the full day, while IL‐2, IFN‐γ, CD71, and CD154 showed fluctuations over the day with a strong inhibition (75%-25%) at 2 h post‐dose. The level of inhibition was variable between patients and could not be related to pharmacokinetic parameters or the presence of regulatory or senescence immune cells. Moreover, the level of inhibition did not correlate with the in vitro tacrolimus drug effect as studied by incubating pre‐dose blood samples with additional tacrolimus. Overall, IL‐2, IFN‐γ, CD71, and CD154 seem to be good markers to monitor residual immune activity of transplantation patients. To evaluate the correlation between these pharmacodynamic biomarkers and clinical outcome, prospective observational studies are needed.